2022
DOI: 10.1111/jopy.12721
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in social power: Links with beliefs about emotion and emotion regulation

Abstract: Objective People differ in how they regulate their emotions, and how they do so is guided by their beliefs about emotion. We propose that social power—one's perceived influence over others—relates to one's beliefs about emotion and to emotion regulation. More powerful people are characterized as authentic and uninhibited, which should translate to the belief that one should not have to control one's emotions and, in turn, less suppression and more acceptance. More powerful people are also characterized as self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Finally, it will be critical to better understand the antecedents of affect regulation, including antecedents that are biological (e.g., genes; Southwick & Charney 2012), situational (e.g., environmental affordances; Suri et al 2018, Uusberg et al 2019, and psychological (e.g., beliefs about emotions, personality, self-efficacy, or goals; Bonanno et al 2015, Carver & Connor-Smith 2010, John & Eng 2014. The beliefs people hold about their emotions might be especially impactful in that they simultaneously affect multiple aspects of affect regulation (Ford & Gross 2019, Zerwas et al 2022. For example, the belief that one can control one's emotions may shape affect regulation identification, selection, and implementation success (Ford et al 2018b, Gutentag et al 2017.…”
Section: Affect-regulation Processesmentioning
confidence: 99%
“…Finally, it will be critical to better understand the antecedents of affect regulation, including antecedents that are biological (e.g., genes; Southwick & Charney 2012), situational (e.g., environmental affordances; Suri et al 2018, Uusberg et al 2019, and psychological (e.g., beliefs about emotions, personality, self-efficacy, or goals; Bonanno et al 2015, Carver & Connor-Smith 2010, John & Eng 2014. The beliefs people hold about their emotions might be especially impactful in that they simultaneously affect multiple aspects of affect regulation (Ford & Gross 2019, Zerwas et al 2022. For example, the belief that one can control one's emotions may shape affect regulation identification, selection, and implementation success (Ford et al 2018b, Gutentag et al 2017.…”
Section: Affect-regulation Processesmentioning
confidence: 99%
“…A wide body of experimental work has found that individuals in lower power roles or with lower status express emotions less intensely, consistent with the use of expressive suppression by lower power/status individuals (see Hall et al, 2005 for a meta-analysis). In daily life, individuals report using expressive suppression in situations where they feel they have less social power (Catterson et al, 2017), and individuals who feel they have low social power report using expressive suppression more frequently (Petkanopoulou et al, 2012;Zerwas et al, 2023).…”
Section: Expressive Suppression In Contexts Of Social Power/status Di...mentioning
confidence: 99%